2010
DOI: 10.1111/j.1365-294x.2010.04947.x
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two genomes: contrasting patterns of phylogeographic structure in a widely distributed bat

Abstract: One of the most widely distributed bats in the New World, the big brown bat (Eptesicus fuscus) exhibits well-documented geographic variation in morphology and life history traits, suggesting the potential for significant phylogeographic structure as well as adaptive differentiation among populations. In a pattern broadly consistent with morphologically defined subspecies, we found deeply divergent mitochondrial lineages restricted to different geographic regions. In contrast, sequence data from two nuclear loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
70
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 132 publications
6
70
0
Order By: Relevance
“…Nevertheless, we suggest that females show more philopatry than males and that this behavior maintains a stronger structure in mtDNA. The same pattern has been found in other mammalian species (Engelhaupt et al 2009;Gauffre et al 2009;Turmelle et al 2011). Specifically, it has been recorded for some carnivores that increased their distributional range after the emergence of the Isthmus of Panama, and covered extensive areas in the newly colonized continent (Eizirik et al 2001;Tchaicka et al 2007).…”
Section: Discussionsupporting
confidence: 73%
“…Nevertheless, we suggest that females show more philopatry than males and that this behavior maintains a stronger structure in mtDNA. The same pattern has been found in other mammalian species (Engelhaupt et al 2009;Gauffre et al 2009;Turmelle et al 2011). Specifically, it has been recorded for some carnivores that increased their distributional range after the emergence of the Isthmus of Panama, and covered extensive areas in the newly colonized continent (Eizirik et al 2001;Tchaicka et al 2007).…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies have revealed that the demographic history and current geographical distribution of many bats were influenced by ancient climatic changes [16,17]. In mainland China, population genetic structure can often be explained by the influence of local geographical structure.…”
Section: Introductionmentioning
confidence: 99%
“…As the dispersal of most bat species is male-biased, examining the maternally inherited mitochondrial DNA (mtDNA) along with microsatellites can provide insights into genetic population structure. [16,17,20-23]. …”
Section: Introductionmentioning
confidence: 99%
“…Free-ranging bats naturally incur damage from encounters with objects in the environment, and as a consequence of failed predation attempts (Davis 1968). Both captive and free-ranging bats may also be subjected to human-induced wing damage resulting from wing biopsies collected by researchers for genetic studies (e.g., Worthington-Wilmer and Barratt 1996;Turmelle et al 2011), dietary analysis (e.g., Sullivan et al 2006;Cryan and Diehl 2009), or from injuries associated with marking bats . Despite the sometimes severe nature of initial wounding, many injuries to wing tissue appear to heal given sufficient time.…”
Section: Introductionmentioning
confidence: 99%